Synthesis of modal regulators with an observer of Luangberger of a state object - Arakelov, O.; Goncharenko, Boris (My University, 2018)
The solution of the problem of constructing modal regulators for linear multidimensional systems providing D-stability (asymptotic stability) of the control object is given. A constructive solution to the problem of synthesis of D-stabilizer (modal) regulators measured by output control object based on the construction of the facility monitors certain order on the basis of the theory of linear matrix inequalities (LMI).
Keywords: modal control; Luenberger observers; linear matrix inequalities; спостерігачі Луенбергера; модальне керування; лінійні матричні нерівності; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка